1461. Non-Invasive Pneumococcal Pneumonia in the United States, 2013–2014. (26th November 2018) - Matanock, Almea; Gierke, Ryan; Shang, Nong; Watt, James; Alden, Nisha; Petit, Susan; Farley, Monica M; Harrison, Lee H; Schleiss, Katherine; Burzlaff, Kari; Thomas, Ann; Schaffner, William; et al.
Abstract: Background: Surveillance for pneumococcal pneumonia (PP) is challenging due to limitations of available diagnostic tests. Previous studies estimated PP from all-cause pneumonia or invasive pneumonia (i.e., positive S. pneumoniae sterile site culture). In 2014, pneumococcal conjugate vaccine (PCV13) was recommended for adults ≥65 years old. We established population-based surveillance for non-invasive pneumococcal pneumonia (NPP) to estimate disease burden and establish a baseline for PCV13 impact evaluation. Methods: We defined a case as clinically or radiographically confirmed pneumonia, positive pneumococcal urine antigen test (UAT), and no evidence of invasive pneumococcal disease in a hospitalized adult ≥18 years old residing in our surveillance areas, which overlap with active bacterial core surveillance areas representing 17, 000, 000 adults across the United States. We estimated NPP incidence (cases/100, 000 population) using US Census data and applying two adjustment factors: (1) the proportion of pneumonia tested by UAT in sampled facilities to account for the fact not all possible cases are tested and (2) the proportion of pneumonia seen at facilities offering UAT in the catchment area. Results: In 2013–2014, 1, 854 patients met our case definition; median age was 65 years (range 18–102). On average, patients were diagnosed on hospital Day 1 (range −3 to 30 days) and hospitalized for 5 days (range < 1–152). Adjusting the crude incidence of 6/100, 000 (reported UAT cases) by factors 1 and 2, we estimated NPP incidence to be 99/100, 000 population. Clinical Description of Patients with UAT Confirmed NPP ( N 1, 854) Conclusion: Our population-based surveillance system allows us to estimate the incidence of laboratory confirmed NPP. Given imperfect UAT sensitivity, this is an underestimate. A more sensitive and serotype-specific UAT could provide improved detection and understanding of NPP. Nonetheless, NPP surveillance allows us to better understand populations at risk for NPP and establish a baseline to evaluate impact of PCV13 on NPP incidence among adults. Disclosures: L. H. Harrison, Merck: sponsored symposium on pneumococcal vaccines, Speaker honorarium. W. Schaffner, Merck: Member, Data Safety Monitoring Board, Consulting fee; Pfizer: Member, Data Safety Monitoring Board, Consulting fee; Dynavax: Consultant, Consulting fee; Seqirus: Consultant, Consulting fee; SutroVax: Consultant, Consulting fee; Shionogi: Consultant, Consulting fee.